2020
DOI: 10.3390/app10051698
|View full text |Cite
|
Sign up to set email alerts
|

Wideband UHF Antenna for Partial Discharge Detection

Abstract: This paper presents a ultra-high frequency (UHF) antenna for partial discharge (PD) detection and the antenna sensor can be used near a conducting ground wire. The proposed UHF antenna has advantages of easy setup and higher-frequency detection over the high-frequency current transformer (HFCT) sensor. First, a variety of loop-shaped antennas are designed to compare each near field coupling capability. Then, a new UHF antenna is designed based on the loop-shaped antenna, which has the best near field coupling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…The shift in resonance frequencies between simulation and measurement carried out using the vector network analyzer (VNA) is reported and investigated in the recent literature. It is confirmed that the sought cause of discrepancies between simulation and experimental results is related to fabrication and measurement errors [28], [29], [33], [34]. Fig.…”
Section: B Measuring the Antenna Parameters Using Vector Network Anal...supporting
confidence: 56%
“…The shift in resonance frequencies between simulation and measurement carried out using the vector network analyzer (VNA) is reported and investigated in the recent literature. It is confirmed that the sought cause of discrepancies between simulation and experimental results is related to fabrication and measurement errors [28], [29], [33], [34]. Fig.…”
Section: B Measuring the Antenna Parameters Using Vector Network Anal...supporting
confidence: 56%
“…As can be seen, most of the antennas have low gain, which can affect antenna sensitivity in detecting electromagnetic waves emitted by PD activity. In addition, some antennas were likely not implemented for PD detection through experiments to verify their sensitivity, because only simulation results were given in their studies [7], [29]. The advantage of the antenna design presented here over the others summarized in Table 3 is that it has a wider bandwidth with higher gain range within the frequency range of interest for PD events, especially when small radiative sources (as holes and seams) are concerned.…”
Section: Fabrication and Measurement Of The Antenna Prototypementioning
confidence: 99%
“…In ref. [11], a loop structure is investigated versus an HFCT. Both are introduced into the grounding branch.…”
Section: Introduction To Detection Of Partial Dischargesmentioning
confidence: 99%